(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The main purpose of this paper is to study the t-best co-approximation and t-best simultaneous co-approximation in intuitionistic fuzzy normed spaces. We develop the theory of t-best co-approximation and t-best simultaneous co-approximation in quotient spaces. This new concept is employed by us to improve various characterisations of t-co-proximinal and t-co-Chebyshev sets .